PHYSIOLOGICAL AND HISTOPATHOLOGCAL STUDY FOR THE EFFECT OF BARLEY (HORDEUN VULGARE) FLOUR ON INDUCED DIABETIC - & et al., Al-Hamdani (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this study is to evaluate the effect of barley consumption on sugar reduction in diabetic patients in male and female rats. The mice were divided into six groups with 10 mice per group. The mice injected the substance with 200 mg / kg body weight to induce diabetes. The study included 60 mice of both sexes, injected with aloxane and a dose of 200 mg / kg body weight to induce diabetes. The first group was represented by the control group as its members took standard food from the experimental animal food. The second group, which represents the induced control group as its members took the general measure of food, but injected the substance of the aloxane for comparison. While the third and fourth groups were fed an equal mixture of wheat flour and barley in the form of dry paste for both females and males for mice, respectively. The fifth and sixth groups were fed barley flour only for both sexes. Measure both body weight and blood sugar at the beginning and end of the two weeks of the experiment, where it was fed daily with various food treatments mentioned previously. Different blood parameters were measured, The physiological and histological changes of liver, kidney and brain were also studied. The results showed that there was a significant decrease in the percentage of blood clocates in groups with diabetes, and showed groups treated with barley decreased cholesterol and triglyceride with the emergence of changes in the tissue in the liver and kidneys, while the brain appeared in its natural form. Barley has a protective effect against diabetes.